Significant improvement in neuropsychological functions after awake craniotomy in a patient with Oligodendroglioma: A case report - Thomas, Mareike; Scheer, Maximilian; Spindler, Kai; Nieberlein, Laura; Hartwigsen, Gesa; Gussew, Alexander; Schob, Stefan; Prell, Julian; Strauss, Christian; Rampp, Stefan (Interdisciplinary Neurosurgery, 2023)
Objective: The goal of awake craniotomy in glioma patients is sparing of cognitive function. Previous investigations suggest that patients in the postoperative state may reach their preoperative level regarding domain-based criteria. Data on significant postoperative improvement beyond the preoperative level is sparse. This article examines the prospective neuropsychological assessment of a glioma patient who underwent awake craniotomy and has shown functional improvement exceeding preoperative levels. Methods: A 34-year-old patient with high premorbid cognitive function level who underwent awake craniotomy for left frontal oligodendroglioma was neuropsychologically assessed and took part in a fMRI-examination at 3 different time points. Results: Preoperative examination revealed severe isolated impairment of working memory, long-term narrative memory in free recall and recognition, and alertness with intact language production and comprehension. After transient global aphasia in the postoperative state, the follow-up examination showed significant improvement in memory and attention exceeding the preoperative level. Conclusions: Tumor location is an important factor in terms of surgical procedures. Cognitive impairment is, however, not always associated with a specific location. Mechanical pressure of the tumor might have led to the isolated consolidation deficit which fully recovered after tumor removal. Psychological disorders should be taken into account regarding prodromal symptoms of neurooncological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Awake craniotomy; Glioma; Improvement of cognitive functions; Neuropsychological assessment